Age-related changes of the histological structure in the limb bones of the domestic fowl - N. S. Sukhanova (Аграрная наука Евро-Северо-Востока)
To assess the possibility of using the bird bone tissue as a recording structure, the histomorphological parameters of the bone tissue of laying hens of the lohman brown cross from the Kirov region (9 females and 1 male) aged from 1 month to 7.5 years were investigated. The comparison of the cross-sections of the humerus and femur, the phalanx of the toe and tibiotarsus of a 6-year-old individual revealed that tibiotarsus is the least susceptible to resorption. For further research in 7 individuals, this bone was divided into 3 sections (T1, T2 and T3), for each of which the description and measurement of the microstructure of the cross sections was carried out. It was revealed that the process of resorption of the periosteum begins at 2.5 years of age with the appearance of primary osteons. At the age of 3.5 years and later they penetrate into all layers of the periosteum, locating in chains between the lines of arrested growth. At 4.5 years of age, secondary osteons appear in the place of the primary ones, and areas of resorption are formed at the intersection of the Haversian and Volkmann canals. At the age of 5.5 years the medullary bone disappears from the bone cavity, rounded cavities filled with centripetal deposition of new bone tissue at the edges appear within the resorption sites. At the age of 6-7 years, bone tissue degeneration occurs, when the small cavities enlarge and merge into large resorption cavities, up to the complete resorption of the mesost. In the distal part of tibiotarsus (T3), a prolonged apposition of the layers of the periosteum and the latest resorption were recorded. The increase of the thickness of the periosteum and a decrease in the density of the osteon population was revealed by the morphometry of cross sections of the center of diaphysis. The sites of tibiotarsus where the age of females corresponds to the lines of growth layer of the periosteum were determined. The sites with additional lines of the arrested growth were demarcated. It was concluded that the periosteal layer of the domestic fowl tibiotarsus in the distal and proximal sites are suitable as a recording structure.